2017
DOI: 10.1103/physrevb.95.174524
|View full text |Cite
|
Sign up to set email alerts
|

Localized vibrations in superconducting YBa2Cu3O7 revealed by ultrafast optical coherent spectroscopy

Abstract: The interaction between phonons and high-energy excitations of electronic origin in cuprates and their role in the superconducting mechanisms is still controversial. Here we use coherent vibrational time-domain spectroscopy together with density functional and dynamical mean-field theory calculations to establish a direct link between the c-axis phonon modes and the in-plane electronic charge excitations in optimally doped YBCO. The non-equilibrium Raman tensor is measured by means of the broadband "coherent-p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 51 publications
2
11
0
1
Order By: Relevance
“…First, since it is shown that there is extremely enlarged coupling between electronic states and A 1g ‐phonon modes by using dynamical mean field theory (MFT) in high T c superconductors (see, e.g., refs. ), it would be interesting to write electron– A 1 g phonon interaction used here within the MFT in order to see whether it drives a topological phase transition without lifting the valley degeneracy. Second, within this context, the topological phase transition of the spin–orbit‐coupled graphene undergoing a coexistence of Coulomb interaction and staggered potential is investigated with the MFT …”
Section: Resultsmentioning
confidence: 99%
“…First, since it is shown that there is extremely enlarged coupling between electronic states and A 1g ‐phonon modes by using dynamical mean field theory (MFT) in high T c superconductors (see, e.g., refs. ), it would be interesting to write electron– A 1 g phonon interaction used here within the MFT in order to see whether it drives a topological phase transition without lifting the valley degeneracy. Second, within this context, the topological phase transition of the spin–orbit‐coupled graphene undergoing a coexistence of Coulomb interaction and staggered potential is investigated with the MFT …”
Section: Resultsmentioning
confidence: 99%
“…The tale of strongly correlated electronic systems (SCES) [1][2][3][4][5][6] is deeply intertwined to that of cuprate high-T c superconductors (HTcS) [7][8][9][10][11][12][13][14][15][16][17][18][19] simply because the prototypical model for the former is exactly the same as the very minimal model to describe the latter [20]: the 2D Hubbard model [21][22][23]. This very fact has enormously increased the number of studies performed in the last thirty years, that is since the discovery of HTcS, on this model and its extensions (the Emery or p-d model among all others [24][25][26]) and derivatives (the t-J model [27,28], the spin-fermion model [29], .…”
Section: Sces and Composite Operator Methodsmentioning
confidence: 99%
“…Misochko等人 [81,82] 之后的实验结果跟Kurz等 人的结果一致. Novelli等人 [83] 进一步系统的实验 和理论分析了这两个模式跟超导态之间的关系, 确认基本上Cu原子的面外振动模式跟超导态没有 耦合, 而Ba原子的面外振动模式受超导态影响. 并 且 后 者 耦 合 发 生 的 过 程 是 在 准 粒 子 达 到 热 平 衡 的 时 间 尺 度 内. Okano等 人 [84] 还 发 现 利 用 双 泵 浦 脉冲技术, 通过改变泵浦脉冲之间的相对时间还 可以控制这两种声子模式的振幅大小.…”
Section: /∆(T )unclassified